1994
DOI: 10.1002/oa.1390040403
|View full text |Cite
|
Sign up to set email alerts
|

DNA of Mycobacterium leprae detected by PCR in ancient bone

Abstract: We report the extraction and amplification of DNA of Mycobacterium leprae, from ancient skeletal material. The significance of the extraction of ancient bacterial DNA is discussed, as are future directions of research into ancient disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 9 publications
1
35
0
1
Order By: Relevance
“…DNA from the causative organisms, Mycobacterium tuberculosis and M. leprae, can be detected by speciesspecific PCR, and the initial reports (Spigelman & Lemma 1993;Rafi et al 1994) have been confirmed by many investigators, reviewed by Spigelman & Donoghue (2003). Both pathogens have no known environmental reservoir, so their presence indicates infection, if not active disease.…”
Section: Introductionmentioning
confidence: 87%
“…DNA from the causative organisms, Mycobacterium tuberculosis and M. leprae, can be detected by speciesspecific PCR, and the initial reports (Spigelman & Lemma 1993;Rafi et al 1994) have been confirmed by many investigators, reviewed by Spigelman & Donoghue (2003). Both pathogens have no known environmental reservoir, so their presence indicates infection, if not active disease.…”
Section: Introductionmentioning
confidence: 87%
“…Numerous studies now confirm the possibility of extracting and amplifying microbial aDNA from pathogens that may persist within human bones and other tissues (e.g., [6,41]). Microbial DNA disseminated via the bloodstream may become trapped in the mineralized tissue of the skeleton, such as hydroxyapatite, or in protected sites, such as the dental root canal and pulp chamber, where it can Diversity 2017, 9, 46 4 of 30 remain somewhat protected from breakdown.…”
Section: Extraction Of Microbial Adnamentioning
confidence: 99%
“…Bacterial infections can be recognized in archaeological remains, initially by palaeopathology and more recently by microbial ancient DNA (aDNA) [4][5][6]. M. leprae targets Schwann cells, damaging the nerves, and in late infections further damage is caused by the host immune response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations